2017
DOI: 10.3184/174751917x15064232103029
|View full text |Cite
|
Sign up to set email alerts
|

The Ozonolysis of Terpenoids, a Pandora's Box of by-Products

Abstract: The ozonolysis of terpenoids is described and the origins of some by-products are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…In non-polar organic solvents, the aromatic aldehyde product was further oxidized by ozone to the corresponding perbenzoic acid, which subsequently decomposed to benzoic acid. 31 When using a mixture of water and organic solvent, 32 the formal dehydration of the hydroxy hydroperoxide intermediate via Baeyer−Villiger-type fragmentation yields benzoic acid instead of the desired aldehyde (Scheme 1, blue pathway). 4a, 16,33 Having optimal conditions in hand for the aqueous ozonolysis of alkene 1 in the presence of Coolade as the most suitable surfactant, the scope of alkene substrates was examined with other aliphatic and aromatic alkenes (Table 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-polar organic solvents, the aromatic aldehyde product was further oxidized by ozone to the corresponding perbenzoic acid, which subsequently decomposed to benzoic acid. 31 When using a mixture of water and organic solvent, 32 the formal dehydration of the hydroxy hydroperoxide intermediate via Baeyer−Villiger-type fragmentation yields benzoic acid instead of the desired aldehyde (Scheme 1, blue pathway). 4a, 16,33 Having optimal conditions in hand for the aqueous ozonolysis of alkene 1 in the presence of Coolade as the most suitable surfactant, the scope of alkene substrates was examined with other aliphatic and aromatic alkenes (Table 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In non-polar organic solvents, the aromatic aldehyde product was further oxidized by ozone to the corresponding perbenzoic acid, which subsequently decomposed to benzoic acid . When using a mixture of water and organic solvent, the formal dehydration of the hydroxy hydroperoxide intermediate via Baeyer–Villiger-type fragmentation yields benzoic acid instead of the desired aldehyde (Scheme , blue pathway). ,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…Under these conditions, the ozonation of 2 was fast; however, a mixture of products was obtained (Scheme ). , Careful separation of the reaction mixture and analysis of the isolated products revealed that four compounds were obtained in this reaction. It must be noted that the composition of the mixture and the yields of the products changed significantly from batch to batch.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proven that firstly, terpene is attacked by ozone in the place of double bonding, and a primary ozonide (PO) is formed. PO is then decomposed to form the so-called "Criegee intermediate", which is highly reactive and will undergo further reactions, which are still under investigation [8][9][10][11][12]. Some terpenes' oxidation products may remain in a gaseous phase, while others may undergo homogeneous nucleation or condensation on preexisting particles.…”
Section: Introductionmentioning
confidence: 99%